Effect of Housing Investments on the Relationship between Mortgage Financing and Economic Growth in EAC Member Countries - Maina, Ben; Ondigo, Herick; Wanjare, Joshua; Onsomu, Zipporah (Journal of Finance and Accounting, 2023)
Mortgage financing is a critical part of financial systems that contribute to financial markets development and deepening and has potential positive effects on a country’s financial and economic growth. Housing investment is important in an economy as it influences on savings, employment, labor productivity and total investment. This study sought to establish the effect of housing investments on the relationship between mortgage financing and economic growth in EAC member countries. The study adopted the Theory of Investment Multiplier. The researcher utilized a positivist research philosophy and both a descriptive and explanatory research designs. Secondary data was gathered through country-specific Central Bank reports, World Bank reports, IMF reports, as well as Africa Development Bank (AfDB) reports between January 2001 and December 2020. Descriptive statistics, correlation analysis, and panel data model estimations were conducted. The study concluded that the association is statistically significant. Failure to reject the hypothesis implies that housing investments does not mediate the relationship between mortgage financing and economic growth among EAC member countries. The study recommends decision makers to come with measures aimed at boosting value of mortgage accounts in the EAC community member countries, as this will translate in growth in real estate sector and perhaps other sectors in the economy. Keywords: Housing Investments, Mortgage Financing & Economic Growth